Pelaksanaan Pembelajaran Penjas Masa Pandemi Covid-19 SMP Negeri di Kecamatan Lasem Tahun 2022 - Ana sulistyaning asih; Roas Irsyada (Universitas Negeri Semarang, 2022)
The purpose of this study was to determine the implementation of physical education learning during the covid-19 pandemic in SMP negeri in Lasem district, Rembang Regency in 2022. This research method is qualitative descriptive, using survey methods. Data collection techniques through observation, interviews, documentation, and questionnaires. This research sample is in SMP Negeri in Lasem district. The results of this study show that the implementation of physical education learning during the covid-19 pandemic in SMP Negeri throughout Lasem district experienced many implementation adaptations adapted to the conditions and regulations governing learning. Physical education teachers must have specific strategies to deal with this condition. The results of the study concluded, 1) Physical Education Learning experienced problems during the covid-19 pandemic, 2) Physical Education teachers applied special strategies during learning during the covid-19 pandemic, 3) Learning experienced situation adaptation according to the applicable official provisions, 4) student learning motivation changed due to constraints in physical education learning.